Solving ‘wicked’ problems: can social learning catalyse adaptive responses to climate change? - Epp, Marissa van; Garside, Ben (International Institute for Environment and Development, 2016)
Social learning approaches can catalyse knowledge co-creation and action, so have the potential to help solve complex ‘wicked’ problems such as climate change and food insecurity. Social learning is more than just group learning; it has an agenda for wider change. It encourages stakeholders to work together to implement and test solutions through iterative cycles of learning, action and reflection.~This working paper synthesises evidence from five diverse initiatives employing social learning approaches in response to such problems using the Climate Change and Social Learning initiative’s monitoring and evaluation framework. It finds initial evidence that key factors in social learning approaches can lead to clear learning outcomes with resulting positive changes in values and practice. Links to longer-term development outcomes are also evident in several completed initiatives.~This paper provides a synthesis across the five initiatives, including a short summary of each. A case study 'compendium' exploring in more detail a total of eight case studies from the five initiatives is available separately and can be reached by clicking by clicking on the first link below.